Violence in schools - Page, Jonathan; Daniels, Jeffrey A.; Craig, Steven J. (SpringerBriefs in Psychology,, 2015)
This forward-looking monograph distills the current knowledge base on lethal school shootings for school professionals invested in improving school safety. Divided between correlates, interventions, and prevention, it begins with the Virginia Tech massacre as exemplifying the kinds of personal, environmental and social dynamics that commonly result in lethal violence on campus. Bullying as a causal factor in school violence is a specific focus of the findings, including immediate and long-term negative effects, psychology of bullies and victims and issues related to cyber bullying. And specialized chapters provide details on Trauma-Focused Cognitive Behavioral Therapy for victimized children and youth, treatment possibilities for bullies and an empirically-supported program for preventing further lethal events.  Featured in this reference:  Case study: Cho Seung-Hui. Correlates of school violence: bullying, psychopathy, ethnic and gender issues and more. Anti-bullying interventions. Treatment of traumatized children. Averted school shootings and resolved school hostage events. The Safe Schools Communities Model for violence prevention. For professionals working in and with schools in various capacities, optimizing safety is a top priority. Violence in Schools gives those readers clear direction toward achieving this crucial goal.